Sistemski in upravno-procesni izzivi uveljavljanja pravic iz zavarovanja za dolgotrajno oskrbo - Babšek, Matej (Podjetje in delo, 2024)
Long-term care is an area that has not been adequately regulated neither in social reality nor in social lawin Slovenia for a long time. That is why the new Long Term Care Act (ZDOsk-1), adopted in 2023, was long-awaited.The article examines systemic and, in particular, procedural legal questions regarding measures in the field of long-term care, for which social work centres are mainly responsible, above all through the newly regulated one-stop-shop. Through the use of different methods, normative, historical, comparative, statistical and case studies, the single entry point and selected new institutes of ZDOsk-1, such as the eligibility assessment and the plan of recommended long-term care services and the personal plan, are analysed. This is based on the importance of procedural regulation, which should ensure substantive legal goals, as well as the protection of constitutional guarantees within the legal and social state. The results, including a comparison of experience in the enforcement of the Exercise of Rights from Public Funds Act and the system of principles and rules under the General Administrative Procedure Act, show for theZDOsk-1 that the institutes in question are not completely deliberate. They are standardised vaguely and inadequately in a broader legislative sense, which will result in problems at the implementation level, especially in terms of accessibility and protection of the procedural positions of parties in these procedures. The findings presented in the paper are useful for legal theory, as well as for public policy makers and practitioners in the field of social welfare in general.
Keywords: center za socialno delo; dolgotrajna oskrba; enotna vstopna točka; long-term care; one-stop shop; posebni upravni postopek; social insurance; social rights; social work centre; socialne pravice; socialno zavarovanje; special administrative procedure